Scheme Design and Kinematics Analysis of Single Leg Mechanism of Multi-legged Robot - Jiman Luo; Zeming Liu; Hui Yin; Shiheng Liu; Li'na Cong (Jixie chuandong, 2021)
In order to realize the monitoring and maintenance of the internal environment of the pipeline，a cam-linkage mechanism is designed as a multi-legged pipeline robot，and the motion analysis and mechanism improvement of the single-leg mechanism are carried out，so as to improve the shortcomings of the initial connecting rod mechanism，such as low motion precision and large inertia force. The mechanism scheme is theoretically modeled，and then the motion analysis of the mechanism is carried out by using the method of the joint simulation of 3D modeling software SolidWorks and motion analysis software Adams. The mechanism is improved by changing relevant parameters of the mechanism. Through comparative analysis，it can be seen that the cam-linkage scheme has more advantages than the initial scheme. Change the size of the cam，the foot of the mechanism in the normal direction of the displacement of the greater，the foot will be lifted higher，and the same time can walk a longer distance. The results also show that the cam-linkage mechanism has less inertia force and impact，more stable operation，and easy to realize specific motion law.